Where'd you go, Bernadette [videorecording (DVD)] - Linklater, Richard, 1960-; Blanchett, Cate, 1969-; Crudup, Billy, 1968-; Wiig, Kristen, 1973-; Greer, Judy, 1975-; Fishburne, Laurence, III, 1961-; Nelson, Emma (Actor); Semple, Maria (20th Century Fox Home Entertainment, 2019)
Bernadette Fox, a loving mom, becomes compelled to reconnect with her creative passions after years of sacrificing herself for her family. Bernadette's leap of faith takes her on an epic adventure that jump-starts her life and leads to her triumphant rediscovery.